Effectiveness of statin intensive therapy in type 2 diabetes mellitus with high visit-to-visit blood pressure variability. Issue 7 (July 2021) - Ikeda, Shota; Shinohara, Keisuke; Enzan, Nobuyuki; Matsushima, Shouji; Tohyama, Takeshi; Funakoshi, Kouta; Kishimoto, Junji; Itoh, Hiroshi; Komuro, Issei; Tsutsui, Hiroyuki
Abstract : Background: Intensive lipid-lowering therapy is recommended in type 2 diabetes mellitus (T2DM) patients with target organ damage. However, the evidence is insufficient to stratify the patients who will benefit from the intensive therapy among them. High visit-to-visit variability in systolic blood pressure (SBP) is associated with increased risk of cardiovascular events. We investigated the effectiveness of intensive versus standard statin therapy in the primary prevention of cardiovascular events among T2DM patients with retinopathy stratified by visit-to-visit SBP variability. Methods: The standard versus intensive statin therapy for hypercholesterolemic patients with diabetic retinopathy study was the first trial comparing statin intensive therapy targeting low-density lipoprotein cholesterol (LDL-C) <70 mg/dl and standard therapy targeting LDL-C ≥100 to <120 mg/dl in T2DM patients with retinopathy without known cardiovascular disease. Using this dataset, we divided the patients into two subpopulations based on standard deviation (SD) and average real variability (ARV) of clinic SBP within the initial 6 months. Results: In a total of 4899 patients, 240 composite cardiovascular events were observed during a median follow-up of 37.3 months. In multivariable-adjusted model comparing intensive versus standard therapy, the hazard ratios for composite cardiovascular events were 0.64 (95% CI 0.45–0.90) and 1.21 (95% CI 0.82–1.80) in patients with high and low SBP variability as defined by SD, respectively. Interaction between SBP variability and statin therapy was significant ( P  = 0.018). The analysis using ARV of SBP showed similar results. Conclusion: Statin intensive therapy targeting LDL-C <70 mg/dl had benefits in primary prevention of cardiovascular events compared with standard therapy among T2DM patients with retinopathy having high, but not low, visit-to-visit SBP variability. Abstract : Supplemental Digital Content is available in the text